1998
DOI: 10.3109/08916939808995367
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 and NF-kB Regulation in Rheumatoid Arthritis and Murine Collagen-Induced Arthritis

Abstract: The DNA binding activity of AP-1 and NF-kappaB are markedly increased in both CIA and RA. In CIA, activation of AP-1 and NF-kappaB precede both clinical arthritis and metalloproteinase gene expression. NF-kappaB expression correlated better than AP-1 with metalloproteinase expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
232
1
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(246 citation statements)
references
References 44 publications
9
232
1
4
Order By: Relevance
“…Studies on several animal models of inflammation support the notion that NF-B plays a physiologic role in inflammatory responses in vivo. For example, NF-B has been shown to be involved in carrageenan-induced pleurisy in rats (16), while synovial NF-B activation occurs within a few days after immunization in a rat adjuvant arthritis model (17) and precedes the development of clinical joint involvement in a murine collagen-induced arthritis model (18). NF-B is also highly activated at sites of inflammation in several diseases and contributes to the duration of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on several animal models of inflammation support the notion that NF-B plays a physiologic role in inflammatory responses in vivo. For example, NF-B has been shown to be involved in carrageenan-induced pleurisy in rats (16), while synovial NF-B activation occurs within a few days after immunization in a rat adjuvant arthritis model (17) and precedes the development of clinical joint involvement in a murine collagen-induced arthritis model (18). NF-B is also highly activated at sites of inflammation in several diseases and contributes to the duration of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The housekeeping gene ␤-actin was used as an internal control. Total RNA (7 g) was reverse-transcribed into complementary DNA by using oligo(dT) [12][13][14][15][16][17][18] primer (Invitrogen) and Superscript II reverse transcriptase (Invitrogen). Complementary DNA (1 l) was amplified by PCR using Taq polymerase (Promega, Madison, WI) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In a murine collagen-induced arthritis and in a rat adjuvant-induced arthritis model, it has been shown that the clinical manifestation of the disease is preceded by NF-kB activation. 61 A lot of effort has been invested to understand the upstream component responsible for NF-kB activation in the synovial tissue. IKK2 is the main kinase involved in cytokine-induced NF-kB activation in fibroblast-like synoviocytes.…”
Section: Nf-jb In Arthritismentioning
confidence: 99%
“…NF-jB is activated in dorsal root ganglia (DRG) after partial sciatic nerve injury and is crucial for hyperalgesia [4,20]. Thus, NF-jB is regarded as one of the most important targets for therapeutic intervention against inflammatory diseases such as rheumatoid arthritis, asthma, or inflammatory bowel disease [1,8,33,35,40].…”
Section: Introductionmentioning
confidence: 99%